Effectiveness and safety of unilateral endobronchial valve applying to severe emphysema: a meta-analysis - Chen, Wei-Song; Zhu, Dan; Chen, Hui; Luo, Jian-Feng (Journal of Emergency and Critical Care Medicine, 2018)
Background: Bronchoscopic lung volume reduction (BLVR) is now deemed to be better for severe emphysema patients when comparing to surgical lung volume reduction surgery (LVRS). This article aims to evaluate the effectiveness and the safety of BLVR using unilateral one-way endobronchial valve (EBV) by a meta-analysis. Methods: We performed a systematic search of available databases, including PubMed, EMBASE, the Cochrane Library, and four domestic databases up to January 28th 2018. Two reviewers viewed all references according to selection criteria independently. The handbook of Cochrane quality assessment system was used to assess the quality of each literature. Randomized controlled trials (RCTs) data were combined and performed for a meta-analysis by using RevMan 5.3 software. Results: This meta-analysis included nine studies. Forced expiratory volume in 1 second (FEV1) in the intervention group improved when comparing with the EBV used control group [standardized mean difference (SMD) =0.57, 95% confidence interval (CI): 0.29–0.86]. Six-minute walking distance (6MWD) [mean difference (MD) =62.35, 95% CI: 32.48–92.22] also improved. And the St. George’s Respiratory Questionnaire (SGRQ) score in the intervention group decreased (MD =−5.54, 95% CI: −7.41 to −3.67). Six months follow-up RCTs reported incidence rates of pneumothorax, hemoptysis, chronic obstructive pulmonary disease (COPD) exacerbation with hospitalization were higher in the BLVR (EBV) group, relative risk (RR) =10.11 (95% CI: 3.46–29.54), RR =5.71 (95% CI: 1.35–24.20), RR =1.96 (95% CI: 1.15–3.32), respectively. And incidence rates of death, massive hemoptysis, pneumonia, COPD exacerbation without hospitalization and respiratory failure between two groups had no significant difference. Conclusions: BLVR using one-way EBV but not intrabronchial valve (IBV) may be an effective and safe procedure for treating COPD patients with severe emphysema.